The Effect of Tonsillectomy on the Morbidity from Recurrent Tonsillitis - Douglas, Catriona M. (Clin Otolaryngol, 2017)
BACKGROUND: Tonsillitis is a common condition with an incidence in UK general practice of 37 per 1000 population a year1. Recurrent tonsillitis results in significant morbidity and impacts on individuals’ quality of life. This study assesses the morbidity and quality of life of adults with recurrent tonsillitis, and the impact of surgical intervention on their health state. OBJECTIVES: 1. To describe disease specific and global quality of life for adults with recurrent tonsillitis six months after tonsillectomy, using two instruments: the Health Impact of Throat Problems (HITP) and EuroQol-visual analogue scale (EQ-VAS) questionnaire. 2. To assess the overall health benefit from tonsillectomy as an intervention using the Glasgow Benefit Inventory (GBI). 3. To assess potential predictors of tonsillectomy benefit. DESIGN: A prospective, observational cohort audit of patients who have fulfilled Scottish Intercollegiate Guideline Network (SIGN) criteria for tonsillectomy2. Setting: Secondary care, teaching hospital Participants: Seventy patients (57 female), median age 20 years (range 13-41). RESULTS: Median pre-operative HITP was 47 (range 15-67), compared to 4 (0-72), (p< 0.001) 6 months following surgery. Median HITP difference was 39.5 (range -20 to 75). There was no significant change in global Quality of Life. Median overall 6 months GBI was 39 (-3-100). Patients had an average of 27 episodes of tonsillitis over a period of seven years before “achieving” tonsillectomy, significantly higher than the SIGN guidelines of three or more episodes over three years. CONCLUSIONS: Recurrent tonsillitis causes a poor disease specific quality of life. Patients experienced a median of three episodes per year for seven years before tonsillectomy. Following tonsillectomy, patients had a significant improvement in their disease specific quality of life. Baseline HITP significantly improved after tonsillectomy. The results imply patients with recurrent acute tonsillitis may be experiencing undue delay